2021
DOI: 10.1111/psj.12445
|View full text |Cite
|
Sign up to set email alerts
|

Narrative strategies in a nondemocratic setting: Moscow’s urban policy debates

Abstract: The Narrative Policy Framework (NPF) explains the role of narratives in policy processes. The NPF was developed for democratic contexts and has not been systematically applied in a nondemocratic setting. This study fills this gap with an empirical analysis of narrative strategies used by governmental and oppositional actors in urban policy debates in Moscow. Results show how governmental actors consistently use angel shifts, contain issues, and avoid using causal mechanisms, while actors opposing governmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 83 publications
2
25
0
1
Order By: Relevance
“…The narrative elements used on both sides reflect these conflict expansion and containment strategies and are consistent with results of other NPF studies in democratic institutional settings and other policy issues (Gupta et al., 2014; McBeth et al., 2007; Shanahan et al., 2013; Stephan, 2020). Our findings also confirm recent NPF applications in nondemocratic institutional contexts that show that government actors use conflict containment strategies and oppositional actors use strong conflict expansion strategies to criticize government‐driven reforms (Schlaufer et al., 2020).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The narrative elements used on both sides reflect these conflict expansion and containment strategies and are consistent with results of other NPF studies in democratic institutional settings and other policy issues (Gupta et al., 2014; McBeth et al., 2007; Shanahan et al., 2013; Stephan, 2020). Our findings also confirm recent NPF applications in nondemocratic institutional contexts that show that government actors use conflict containment strategies and oppositional actors use strong conflict expansion strategies to criticize government‐driven reforms (Schlaufer et al., 2020).…”
Section: Discussionsupporting
confidence: 88%
“…Schlaufer et al. (2020) has shown that in an authoritarian institutional context, public policy debates typically revolve around policy reforms initiated by the government. Therefore, government actors tend to use conflict containment strategies that support reform‐focused policy positions.…”
Section: Theoretical Framework and Expectationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though recent research indicates that policy narratives and proposals can be analyzed in Russia at a local level (Schlaufer et al. 2021 a, b), the challenges of collecting data on preferences and behavior of policy actors in higher positions in authoritarian systems remain.…”
Section: Research Design and Methodologymentioning
confidence: 99%